Investigation of Rheological and Leaching Characteristics of Ash at Higher Concentrations - Singh, Gurprit (My University, 2018)
Coal is the world's most abundant fossil fuel and its reserves are distributed in all the continents. During combustion of coal in the thermal power plants generate large amount of bottom ash and fly ash, which have low value for utilization and several environmental problems associated with their deposition. The quality of the coal ash depends on the properties of coal, combustion efficiency, pulverized coal feed and proper quality control in maintaining the particle size etc. The available Indian coal quality is very poor; generate the large quantities of ash produced as byproducts of combustion. With increasing in the demand of the coal as fuel in thermal power plants combustion products, fly and bottom ash become a serious environmental problem due to their leaching characteristics. The huge amount of coal ash (fly and bottom) is generated every year worldwide whereas only a small amount of coal ash is utilized for various applications like cement, road and flyover embankments, bricks, concrete etc. Currently in India, about 60% of fly ash is used and remaining ash disposed into ash pond. The disposing of ash requires large amount of water and land. The disposal of fly ash in the thermal power plant is a challenging task. Presently coal ash with water is transported through pipeline in ash disposal system with very low solid concentration, which consumes huge amount of water and pumping energy but also causes serious environmental problems at the disposal site. The objectives of the present study was to investigate the rheological and leaching characteristics of the fly and bottom ash at high solid concentration with an additive of sodium bicarbonate. The various physio-chemical and mineral properties were investigated to find out possibility of utilization for various applications. The fly and bottom ash samples collected from different thermal power plants namely Guru Nanak Dev thermal power plant, Bhatinda, Punjab, Guru Gobind Singh Super Thermal Power Plant, Ropar, Punjab, Guru Hargovind Singh thermal power plant, Lehra Mohabbat, Punjab and Deenbandhu Chhotu Ram thermal power plant, Yamuna nagar, Haryana. In present work, environmental risk analysis of disposal ash was carried out to predict various critical issues associated with disposal of ash. Standard leaching testing procedure like ASTM-D3987 (American Society of Testing and Materials), EP-3050B (Extraction Procedures) and TCLP-1311 (Toxicity Characteristic Leaching Procedure) were used to investigate the leaching characteristics of fly and bottom ash. The leaching characteristics of fly and bottom ash was determined at different liquid to solid ratio of 20:1 to 60:1, leaching time vi duration (5-20 days) and temperature (25-40ºC). The influence with addition of additives on leaching characteristics of fly and bottom ash was carried out by using sodium bicarbonate as additive. The proportion of additive was varied from 0.2-0.6% (by weight). The concentration of leachate elements like Mn, Mg, Cr, Zn, Cu, Ni, Pb, Co, Fe and Mo increased with increase in liquid-to-solid ratio, leaching time duration and temperature for fly and bottom ash suspension. It was also observed that leachability of trace elements were affected by the pH of extraction solution. This may be attributed that metal solubility increases with decrease in pH value. Minimum leachability of the solution was observed with ASTM method, whereas maximum with TCLP method at (L/S) ratio 60:1. It was noticed that addition of additive (NaHCO3) in very small proportion helps to minimize the leaching potential hazards caused by trace elements present in fly and bottom ash. The pH value of slurry suspension was increased with addition of NaHCO3 and contributed in decreasing the leaching of trace elements. The rheological characteristics of fly and bottom ash suspension was determined using standard rheometer (Anton Paar) at different solid concentration of 10-60% (by weight). Fly ash samples exhibit Newtonian behaviour up to 30% solid concentration. Beyond this it depicted non-Newtonian flow characteristics whereas bottom ash suspensions showed Newtonian behavior up to 40% solid concentration (by weight). Relative viscosity of both fly and bottom ash slurry suspensions were increased more rapidly at higher solid concentration as compared to lower solid concentration. Results indicate that addition of additive at higher solid concentration was more effective as compared to lower solid concentration of both fly and bottom ash suspension. Optimal reduction in relative viscosity was noticed with the 0.4% addition of additive. Darby and Melson (1981) empirical correlation was used to predict the head loss in slurry pipeline of 100 m length with 100 mm diameter for fly and bottom ash suspension. The head loss was predicted by taking solid concentration from 10-60% (by weight) and flow velocity 0.5 to 4.5 m/sec. It was observed that as the solid concertation and flow velocity increased head loss in slurry pipe line also increased.
Keywords: Rheology; Leaching; ash; Pressure drop; Traced Element